Rádio on-line: um estudo ecossistêmico do meio radiofônico na internet - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
Radio since its beginning presented itself as an important mean of communication in the modern society. Nowadays, keeping up to technological convergence it is resetting up accordingly to new digital trends. This present dissertation brings observations about the radio under the ecosystemic point-of-view in Internet times. In order to deal with the subject, it begins with the willingness in accepting the radio through it specific language (voice, music, sound effects and silence) regardless the technological platform in which it is bound, as defined by Ferraretto and Kischnhevsky. The research objective was to understand the radio medium inserted in the Internet environment as autopoietic system of contemporaneity. In order to do so, first, the structural and technological changes and transformations it suffered when it was inserted on the web were described. Subsequently, two different types of online radios were chosen: radio in the web and web radio to introduce the aspects about message, reception, market and regulation. This stage was done through the observation of the most listened radios via Internet registered on radios.com.br. From then on, with the theoretical mark based on Niklas Luhmann Social Systems Theory and on the inductive method, it was pointed which couplings and autopoiesis the radio has been put through in the online world. As a result it was identified that the web radio as well as podcast are originated from auto reference and structural couplings that the radio did in order to keep itself alive in an evolved way in the digital environment.
Keywords: Rádio na Internet; Web rádio; Ecossistemas Comunicacionais; Rádio; Radio on the Internet; Web radio; Communicational Ecosystems; CIÊNCIAS SOCIAIS APLICADAS: COMUNICAÇÃO